2015
DOI: 10.1371/journal.pone.0114947
|View full text |Cite
|
Sign up to set email alerts
|

Recalibration of the Limiting Antigen Avidity EIA to Determine Mean Duration of Recent Infection in Divergent HIV-1 Subtypes

Abstract: BackgroundMean duration of recent infection (MDRI) and misclassification of long-term HIV-1 infections, as proportion false recent (PFR), are critical parameters for laboratory-based assays for estimating HIV-1 incidence. Recent review of the data by us and others indicated that MDRI of LAg-Avidity EIA estimated previously required recalibration. We present here results of recalibration efforts using >250 seroconversion panels and multiple statistical methods to ensure accuracy and consensus.MethodsA total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
127
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(136 citation statements)
references
References 55 publications
7
127
0
2
Order By: Relevance
“…6 However, the results in this study were similar to the newly published study, 1.6%, 6 though the recently published study by the CDC did not stratify the FRR results by infecting subtype. A previous study from Vietnam showed a very low FFR for the BED Capture EIA (BED-CEIA), 7 and though the results of the BED-CEIA and LAg-Avidity assay are highly correlated, it is notable that the BED-EIA has a higher FRR than the LAg-Avidity.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…6 However, the results in this study were similar to the newly published study, 1.6%, 6 though the recently published study by the CDC did not stratify the FRR results by infecting subtype. A previous study from Vietnam showed a very low FFR for the BED Capture EIA (BED-CEIA), 7 and though the results of the BED-CEIA and LAg-Avidity assay are highly correlated, it is notable that the BED-EIA has a higher FRR than the LAg-Avidity.…”
supporting
confidence: 73%
“…4 Specifically, the test developers recommends a cutoff of a 1.5 normalized optical density (OD-n) and subsequent viral load confirmation (viral load >1,000 copies/ ml). 5,6 An additional recommendation is the generation of a local false-recent rate (FRR), which is the fraction of longterm infected (>2 years) who test positive for the testing algorithm. 5,7,8 In this report, we present LAg-Avidity assay results from individuals in Guangxi province of China who have been infected a median of 5.4 years (range 2.0 to 13.5 years), based on prior HIV antibody testing.…”
mentioning
confidence: 99%
“…Although there was no statistically significant difference between the two assays, the point estimates for the LAg-Avidity EIA PFR were lower than the BED-CEIA, which complements previous demonstrations of improved performance characteristics of the LAg-Avidity EIA compared with the BED-CEIA. 16,25 The better performance of LAg-Avidity EIA is likely attributed to the design of the assay to measure HIV antibody avidity compared to the BED-CEIA, which is a capture EIA that measures the proportion of anti-HIV IgG to total IgG.…”
Section: Discussionmentioning
confidence: 99%
“…These were 33%, 32%, and 52% lower than published estimates of 287 (248–328), 152 (128–178), and 298 (262–338) days for respective assays of clade C samples. 1,3,6 Other analyses (data not shown) showed that MDRIs do not differ significantly with the estimation method.…”
mentioning
confidence: 88%
“…1 A case is defined as recent when the optical density, or avidity index, measured using a chosen biomarker, is less than some preset cutoff ( C ). In southern Africa, MDRI values were first estimated for the multi-subtype peptide representing subtypes B, E and D (BED)-capture enzyme immunoassay using samples collected in Harare from 1997 to 2000 during the Zimbabwe Vitamin A for Mothers and Babies (ZVITAMBO) trial.…”
mentioning
confidence: 99%